Analysis of the Direct Effect of Perceived Usefulness and Perceived Ease of Use on Intention to Use with Attitude Mediation in Digital Banking - Ghazali, Azhar; Manggabarani, Alfatih Sikki; Saragih, Guntur Syahputra (Yayasan Sinergi Kawula Muda, 2026)
This study examines the determinants of intention to use digital banking services within the Technology Acceptance Model (TAM) framework, focusing on perceived usefulness (PU), perceived ease of use (PEOU), and attitude (ATT). As digital banking adoption grows rapidly in Indonesia amid the regional expansion of fintech innovations across Southeast Asia, understanding the behavioral mechanisms behind adoption becomes increasingly significant for both information systems and management research. A quantitative approach was applied using survey data from 210 active digital banking users in Jakarta, analyzed through Structural Equation Modeling (SEM) with SmartPLS 4.0. The results show that ease of use has a significant positive impact on users’ intention to adopt digital banking, emphasizing the importance of intuitive system design and low-effort interaction. Meanwhile, usefulness and attitude were found statistically insignificant in predicting intention, indicating that functional benefits alone may not directly drive user behavior. Rather than drawing conclusions about user priorities, these findings suggest a more complex interplay between cognitive and experiential factors. The study extends TAM by highlighting the contextual influence of user experience and cultural expectations in emerging digital economies beyond Indonesia. Practically, financial institutions are advised to enhance usability through seamless navigation, efficient processes, and reduced cognitive barriers to strengthen engagement and long-term adoption.